Evaluasi User Experience Dan User Interface Aplikasi Laporkitong Dengan End User Computing Satisfaction - Wanma, Nuraya; Inan, Dedi Iskandar; Baisa, Lorna Yertas (STMIK Banjarbaru, 2024)
The Lapor Kitong website has been around since 2022, but it is necessary to evaluate the User Experience and User Interface (UI/UX) to ensure optimal use of this platform. The study aims to determine the level of satisfaction of UI/UX with the LAPORKITONG application, by utilizing the End User Computing Satisfaction (EUCS) method which is measured using Partial Least Square Structural Equation Modeling (PLS-SEM). By distributing online questionnaires for two months, 168 valid respondents using the application were obtained. The results of the analysis show that of the five factors determining the level of satisfaction measured, only accuracy and ease of use have a statistically significant effect on the level of satisfaction with using the application. However, the results of the coefficient of determination (R)2 show that the independent variables used are quite significant in predicting the satisfaction level, namely 68.4%. This show that the need for the level of accuracy and ease of use of the platform is something that is of great concern and determines the experience of using it for the people of West Papua. Keywords: Laporkitong; User Experience; User Interface; End User Computing Satisfaction; Partial Least Square Structural Equation ModelingÂ AbstrakWebsite Lapor Kitong sudah ada semenjak tahun 2022, namun perlu dilakukan evaluasi terhadap User Experience dan User Interface (UI/UX) untuk memastikan penggunaan platform ini semakin optimal. Penelitian ini bertujuan untuk mengetahui tingkat kepuasan (satisfaction) UI/UX terhadap aplikasi LAPORKITONG, dengan metode End User Computing Satisfaction (EUCS) diukur menggunakan Partial Least Square Structural Equation Modelling (PLS-SEM). Penyebaran kuesioner online dilakukan dua bulan dan 168 responden pengguna aplikasi tersebut yang valid. Hasil analisis dari lima faktor penentu tingkat kepuasan yang diukur, hanya accuracy dan ease of use yang berpengaruh signifikat terhadap tingkat kepuasan penggunaan. Hasil coefficient of determination (R)2 menunjukkan variabelâ€“variabel independen yang digunakan cukup signifikan memprediksi satisfaction level, yaitu sebesar 68,4%. Hal ini menunjukkan bahwa kebutuhan tingkat akurasi dan kemudahan penggunaan platform tersebut menjadi hal yang sangat diperhatikan dan menentukan pengalaman penggunaannya bagi masyarakat Papua Barat.Â